2019
DOI: 10.1007/s42452-019-0626-x
|View full text |Cite
|
Sign up to set email alerts
|

Analytical methods for the routinely evaluation of pesticide residues in lemon fruits and by products

Abstract: Citrus fruits and their by-products such as concentrated juices and essential oils are important intermediate by-products in the food industry that can selectively accumulate plant protection agrochemicals employed in their production. They are very difficult matrices for pesticide residue analysis due their high number and concentration of phytochemicals that could hamper the determinations. The fruit processing leads to the concentration/dilution or elimination of some of these natural products that change t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Molecules present at very low levels would require the use of high volumes of by-products, which would imply the accumulation of pesticides. Previously published works have determined the presence of pesticides in by-products derived from processing olives, coffee, oranges, lemons, strawberries, soybeans or cow peas using analytical techniques [ 128 , 129 , 130 , 131 , 132 , 133 ]. Each study used a different weight of biomass and volume of solvent, in addition to using very variable kinds of solvents.…”
Section: Safety Assessment Of Citrus Peels As a Matrix To Recover Asc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecules present at very low levels would require the use of high volumes of by-products, which would imply the accumulation of pesticides. Previously published works have determined the presence of pesticides in by-products derived from processing olives, coffee, oranges, lemons, strawberries, soybeans or cow peas using analytical techniques [ 128 , 129 , 130 , 131 , 132 , 133 ]. Each study used a different weight of biomass and volume of solvent, in addition to using very variable kinds of solvents.…”
Section: Safety Assessment Of Citrus Peels As a Matrix To Recover Asc...mentioning
confidence: 99%
“…Each study used a different weight of biomass and volume of solvent, in addition to using very variable kinds of solvents. The studies that used lower biomass weights (50 mg or 10 g) did not detect pesticides or they were detected below the MRL [ 128 , 130 ]. The studies that used higher biomass weights (25 g, 500 g or 1 kg) found pesticides above the MRL [ 129 , 131 , 132 ].…”
Section: Safety Assessment Of Citrus Peels As a Matrix To Recover Asc...mentioning
confidence: 99%
“…There are some reported studies in literature dedicated to analysis of pesticide residue level in the lemon fruit and lemon products. Based on those studies, registered insecticides including abamectin and buprofezin and non-registered insecticide residues were reported in lemon fruits (Andrascikova & Hrouzkova, 2013;Bakirci et al, 2014;Cicero et al, 2015;Dincay & Civelek, 2017;Besil et al, 2019;Chen et al, 2021;Aslantas et al, 2023;Karaagaçlı, 2023). Moreover, the number of Rapid Alert System for Food and Feed (RASFF) notifications in 2021 for Turkey which was the most reported origin, increased from 191 to 361.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported the residues of different pesticides in these vegetables (Chen et al, 2012;Ali et al, 2019).Consumption of these contaminated vegetables can be hazardous to one's health (Chen et al, 2012), and dietary exposure assessments should be included in routine annual monitoring programs. Different vegetables have different phytochemicals which may possess physicochemical properties similar to targeted pesticides which results in falsepositive results in chromatographic instruments (Besil et al, 2019). Moreover, these phytochemicals may contaminate the sensitive instruments and reduce the selectivity of the analytical method.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these phytochemicals may contaminate the sensitive instruments and reduce the selectivity of the analytical method. Thus for robust and precise quantitation of multiple pesticides, the standard analytical method should be validated for each food commodity before analysis (Besil et al, 2019;SANTE, 2019).…”
Section: Introductionmentioning
confidence: 99%